2019
DOI: 10.3988/jcn.2019.15.3.321
|View full text |Cite
|
Sign up to set email alerts
|

Restless Legs Syndrome in Parkinson's Disease Patients: Clinical Features Including Motor and Nonmotor Symptoms

Abstract: Background and Purpose We investigated the frequency and clinical features of restless legs syndrome (RLS) in patients with Parkinson's disease (PD). Methods This study included 74 PD patients. RLS was diagnosed in face-to-face assessments of all of the subjects based on diagnostic criteria of the International Restless Legs Syndrome Study Group revised in 2003. We analyzed the clinical features of PD patients with and without RLS and compared the data to idiopathic RLS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 33 publications
(47 reference statements)
1
18
2
Order By: Relevance
“…Likewise, other studies have shown no differences in parkinsonian motor symptoms between the two groups. 8,21 However, one study showed a higher HY stage with more severe limb parkinsonism and rest tremor in PD patients with RLS than in those without RLS. 5 The clinical manifestations of PD are heterogeneous and its clinical subtypes have been empirically defined based on the prominent motor symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, other studies have shown no differences in parkinsonian motor symptoms between the two groups. 8,21 However, one study showed a higher HY stage with more severe limb parkinsonism and rest tremor in PD patients with RLS than in those without RLS. 5 The clinical manifestations of PD are heterogeneous and its clinical subtypes have been empirically defined based on the prominent motor symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Research demonstrates that PD patients with RBD had significantly higher rates of anxiety and depression and a higher mean PDSS-2 score compared to ones without (36). Patients with RLS show more scores of depression and anxiety, lower sleep quality, and more autonomic dysfunctions (37).…”
Section: Anxietymentioning
confidence: 95%
“…Restless Legs Syndrome (RLS) is another primary sleep disorder frequently associated with PD. In contrast to RBD, whether RLS is also a risk factor for subsequent development of PD is still a subject of debate ( Alonso-Navarro et al, 2019 ; You et al, 2019 ). True prevalence of RLS in PD is not well established as many mimickers of RLS frequently affect PD patients, such as akathisia, rigidity, and leg cramps ( You et al, 2019 ).…”
Section: Sleep Dysfunction In Neurodegenerative Disordersmentioning
confidence: 99%
“…In contrast to RBD, whether RLS is also a risk factor for subsequent development of PD is still a subject of debate ( Alonso-Navarro et al, 2019 ; You et al, 2019 ). True prevalence of RLS in PD is not well established as many mimickers of RLS frequently affect PD patients, such as akathisia, rigidity, and leg cramps ( You et al, 2019 ). While both RLS and PD respond favorably to dopaminergic medications and are worsened by the administration of dopamine blocking medications, there are sharp differences from a neuropathological standpoint.…”
Section: Sleep Dysfunction In Neurodegenerative Disordersmentioning
confidence: 99%